Analisis Dampak Harga Kedelai terhadap Produksi Tahu dan Tempe pada Pabrik Paguyuban Tahu Tempe Korwil Garut - Agus Suryana (Jurnal Publikasi Ilmu Manajemen, 2025)
The price fluctuation of soybeans as the main raw material has an important role in determining the sustainability of tofu and tempeh production. This research aims to analyze the influence of soybean prices on the production of tofu and tempeh at the Paguyuban Tofu Korwil Garut Tempe Factory. The research uses a quantitative approach with simple linear regression analysis and elasticity analysis. The data used is a monthly simulation data for one year that is analyzed using SPSS software. The results of regression analysis show that the price of soybeans has a negative and significant effect on the production of tofu and tempeh. The regression equation obtained is Y=1140,012−0,062X, which shows that the increase in soybean prices will reduce the amount of production. The determination coefficient value of 0.993 indicates that 99.3% of production variation can be explained by changes in soybean prices. The result of the elasticity calculation shows a value of -1,18, which indicates that the production of tofu and tempeh is elastic to changes in soybean prices. This study concluded that the price of soybeans is the dominant factor that affects the production level of tofu and tempeh. Therefore, soybean price stability is very important to maintain production continuity, especially for small and medium industries.